Gunshot in a yellow-headed caracara (Mivalgo chimachima): case report - Perles, L.; Kawamoto, F. Y. K.; Couto, C.; Werther, K.; Minto, B. W. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2018)
Anthropogenic injuries have been frequentlydescribed in raptorial, including habitat destruction, pollution,car collisions, structure impacts, and poaching by trapor gunshot. (PUNCH, 2001). In Brazil, hunting or trappingof any free-living animal, including birds of prey species isforbiden by the law number 5.197, from January 3th, 1967(INSTITUTO CHICO MENDES DE CONSERVAÇÃODA BIODIVERSIDADE, 2008) and by the art. 29 of theEnvironmental Crimes, Law 9.605/98 (BRASIL, 1998). Inspite of this law, it is frequent in the wild animal clinic toreceive birds with fractures and internal organ damagecaused by firearm projectiles. There are several studies inother countries which demonstrate that hunting is an importantfactor causing mortality of these animals, especiallyraptors (DEEM; TERRELL; FORRESTER, 1998; PUNCH, 2001; WENDEL; SLEEMAN; KRATZ, 2002). This casereport is the description of multiple fractures caused bygunshot in a Yellow-headed caracara (Mivalgo chimachima).